Direct Z-scheme Cs2O–Bi2O3–ZnO heterostructures for photocatalytic overall water splitting. Issue 43 (23rd October 2018) - Hezam, Abdo; Namratha, K.; Drmosh, Q. A.; Ponnamma, Deepalekshmi; Nagi Saeed, Adel Morshed; Ganesh, V.; Neppolian, B.; Byrappa, K.
Abstract : In this work, a direct Z-scheme Cs2 O–Bi2 O3 –ZnO heterostructure without any electron mediator is fabricated by a simple solution combustion route. Abstract : In this work, a direct Z-scheme Cs2 O–Bi2 O3 –ZnO heterostructure without any electron mediator is fabricated by a simple solution combustion route. Cs2 O is chosen as a sensitizer to expand the light absorption range, and in addition, its conduction band minimum (CBM) and valence band maximum (VBM) positions are suitable to construct a direct Z-scheme system with ZnO and Bi2 O3 . Structural and elemental analyses show clear evidence for heterostructure formation. The Z-scheme charge carrier migration pathway in Cs2 O–Bi2 O3 –ZnO is confirmed by high resolution XPS and ESR studies. The fabricated heterostructure exhibits a good ability to split water to H2 and O2 under simulated sunlight irradiation without any sacrificial agents or co-catalysts and has excellent photostability. The apparent quantum efficiency of the optimized Cs2 O–Bi2 O3 –ZnO heterostructure reaches up to 0.92% at 420 nm. The excellent efficiency of this fabricated heterostructure is attributed to the efficient charge carrier separation, the high redox potential of the CBM and VBM benefiting from a direct Z-scheme charge carrier migration pathway and the extended light absorption range.